Does consumer behaviour matters? Online advertising evaluation via predictive analytics - Suparmaniam, Navanit; Zetty Ain, Kamaruzzaman; Cheng, Jack Kie; Siti Sakinah, Mohtar; Mohd Izzat, Shafie @ Mohd Alias; Mohd Jamil, Mohd Ja’afar (GBMR, 2023)
With rapid technological progress, the number of Internet users is increasing. This makes it easy for an internet user to access the internet through their computer, laptop, mobile phone, tablet or other media. The internet is becoming a real advancement of online advertising when there is number of increase internet users. Our extensive reach and contacts make it possible for various online media outlets to be solid advisors in business development. But an increase in the number of Internet users does not mean an increase in Internet purchasing. As a result, it is vital to investigate how online advertising affects consumer buying behavior and influences consumer behavior toward the internet. A survey of Internet users was undertaken to evaluate and test the element that determines consumer behavior toward online advertising. The research was open to the public. The technique applied was quantitative analysis with a sample of 118 people. The analysis of quantitative data involved the use of the SPSS software that generating both descriptive and inferential statistics of results from the data. In addition, predictive analytics via multiple regression analysis was used to analyze the relationship between the independent and dependent variables. The results of this study provide evidence that marketers need to consider the informative, pleasure, and materialism of online advertising when creating online ads. By understanding all the factors that will influence consumer’s behavior towards online advertising, marketer can better create an effective advertisement to influence consumer’s informational responses.